KADAR DEBU AMBIEN DI TERMINAL INDUK KM 6 BANJARMASIN PROVINSI KALIMANTAN SELATAN DAN DAMPAKNYA TERHADAP KESEHATAN MASYARAKAT - Agustina Niswanti; Emmy Sri Mahreda; Ahmad Yamani; T. Atmowijoyo (EnviroScienteae, 2013)
The purpose of this experiment are: 1) To analyze how much ambient dust levels in the vicinity of the Main Terminal Km. 6 Banjarmasin, 2) To analyze the level of air pollution caused by dust in the vicinity of the Main Terminal (Terminal Induk) Km. 6 Banjarmasin, and 3) To analyze the relationship between the amount of dust in the health status of communities in the vicinity of Terminal Parent Km. 6 Banjarmasin. The results showed the highest ambient dust levels obtained at locations Parent km.6 Terminal at 16:00 to 20:00 pm at the time of measurement, which is 984.56 µg/Nm3, followed by measurements at 20:00-24:00 pm and measurement at 4:00 to 8:00 pm, which respectively 927.792 µg/Nm3and 925.87 µg/Nm3. For dust levels in the highest residential areas obtained at the time of measurement at 20:00-24:00 pm, 74.19 µg/Nm3, followed by measurements at 08:00-12:00 pm and measurements at 12:00 - 16:00 pm, respectively at 46.05 µg/Nm3and 41.73 µg/Nm3. Average ambient dust in the Main Terminal Km.6 already exceeds the threshold required under Regulation PP 41 of 1999, amounting to 903.15 µg/Nm3, while in residential areas is still far below the standards required by the 46.88 µg/Nm3. There is a strong relationship between the quality and the very significant ambient dust in the location of Terminal Parent Km. 6 with public health, with r = 0.735 and P significance of 95 %. Meanwhile, in nearby residential areas showed that the weak relationship between ambient dust levels with public health, where r = 0.259 and 0.283 for significance P> 95 %.